1993
DOI: 10.1164/ajrccm/148.4_pt_1.955
|View full text |Cite
|
Sign up to set email alerts
|

Expired Breath Hydrogen Peroxide Is a Marker of Acute Airway Inflammation in Pediatric Patients with Asthma

Abstract: Airway inflammation is important in the development and progression of many pulmonary disorders, including asthma. We hypothesized that the hydrogen peroxide (H2O2) concentration in expired breath may be a marker of airway inflammation. Expired breath condensate was collected by cooling and the H2O2 concentration was measured fluorimetrically. Thirty-five samples were collected from 22 pediatric patients with asthma who were 7 to 18 yr of age and from 11 healthy, nonasthmatic controls. Asthmatic subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 17 publications
8
103
1
2
Order By: Relevance
“…An earlier study found protein contamination of most samples at very low levels (using two dimensional gel electrophoresis) [5]. Other condensate studies have either not attempted to identify contamination [7,15], or have not demonstrated contamination in healthy children [12]. This is the first study to assess potential contamination in children with respiratory disease, however there was no correlation between age or FEV1 and amylase in condensate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…An earlier study found protein contamination of most samples at very low levels (using two dimensional gel electrophoresis) [5]. Other condensate studies have either not attempted to identify contamination [7,15], or have not demonstrated contamination in healthy children [12]. This is the first study to assess potential contamination in children with respiratory disease, however there was no correlation between age or FEV1 and amylase in condensate.…”
Section: Discussionmentioning
confidence: 78%
“…Condensate is capable of carrying molecules <65 kDa [5]: that could include the majority of pro-inflammatory pulmonary cytokines that are increased in CF. Nitrite [6], hydrogen peroxide [7], tumour necrosis factor-a and interleukin (IL)-6 [5] have been measured in breath condensate.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] This noninvasive technique has been advocated as a simple method for documenting airway inflammation. Therefore, the present study was designed to evaluate H 2 O 2 -E in healthy cigarette smokers, and to determine the acute effects of the consumption of one cigarette on H 2 O 2 -E levels.…”
Section: Discussionmentioning
confidence: 99%
“…17 Since then high H 2 O 2 -E levels have been detected under a number of different conditions such as ARDS, asthma and COPD. [6][7][8][9][10] Although such results strongly suggest a role for expired hydrogen peroxide as a marker for respiratory tract inflammation, the number of investigations and publications in the area remains small.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the hydrogen peroxide (H 2 O 2 ) molecule, whose increased presence in human breath could indicate oxidative stress in the lungs [61,62]. Detection of elevated levels of H 2 O 2 can be used for early diagnosis and monitoring of such diseases as asthma [63][64][65], chronic obstructive pulmonary disease [66], or acute respiratory distress syndrome [67,68], a severe inflammatory condition with up to 50 % mortality [69]. The detection of H 2 O 2 in human breath is most commonly performed by the creation of breath condensate and the use of spectrophotometric or spectrofluorometric methods, which achieve detection limits in the range of a few ppb to a few hundred ppb [62].…”
Section: Introductionmentioning
confidence: 99%